Strengthening Literacy of Cultural Arts and Crafts in the Material of Sculpture for 6th-grade Elementary School Students through Learning Video Media - Silmi Nabilah Millatina; Rina Maryanti; Verra Wulandary (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to determine and improve students' understanding of literacy through learning video media. Based on previous research, there are not too many studies that discuss Strengthening Literacy for Learning Arts, Culture and Crafts in Sculpture Artwork Materials for 6th-grade elementary school students. This study uses a quantitative approach to pre-experimental design in the form of pre-test and post-test. Based on the results of the research that has been carried out, before providing an understanding of the material of Sculpture in the students' understanding of Cultural Arts and Crafts learning, the results of the pre-test only reached an average value of 61.0% then an increase occurred after the learning video media was given, the post-test results the test given increased by 90.28%. The results showed that the difference was 29.28%. So, it can be concluded that the use of instructional video media on the material of sculptures learning Arts, Culture and Crafts can improve students' knowledge literacy.